Communication Support And Physiologic Monitoring For Hemiplegic Patients Using Smart Glove - KaviPriya G; Manju Bargavi B; Manojini R; Roshini N; Mrs. Nithya C; Dr. Yuvaraj V (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Hemiplegia, characterized by one-sided paralysis resulting from brain or spinal cord injuries, presents challenges in rehabilitation due to the often gradual and imperceptible nature of improvements. Our proposed project tackles this issue by incorporating various sensors flex, temperature, and pulse sensors to continuously monitor vital information that real time data shared in telegram application using internet of things. This technology not only captures nuanced details of temperature variations, and pulse variations but also enables patients to communication between hemiplegia to hemiplegia people and hemiplegia people to normal people effectively. The project stands out with its real-time communication feature using voice module to communicate with normal people to hemiplegia people and hemiplegia people to hemiplegia people via blinking the lamp. In the presence of abnormal conditions or significant changes in the patient's status, immediate alert messages are sent to caregivers and medical professionals. This ensures timely responses and tailored interventions. The integration of flex sensors for muscle movements, temperature sensors for body temperature variations, and pulse sensors for monitoring the wearer’s heart rate collectively provides a comprehensive understanding of the patient's condition. By bridging the communication gap between hemiplegia patients and care givers, our project aims to revolutionize monitoring and support systems. Through real-time alerts and continuous data tracking, we aspire to significantly improve rehabilitation outcomes and enhance the overall quality of life for those grappling with hemiplegia.